1978
DOI: 10.1039/p19780001117
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis, reactions, and spectra of 1-acetoxy-, 1-hydroxy-, and 1-methoxy-indoles

Abstract: Reduction of 2-nitrophenylacetaldehyde gave the unstable 1hydroxyindole, trapped as 1 -acetoxyindole. Concurrent alkaline hydrolysis with methyl iodide present yielded 1 -methoxyindole which was substituted by electrophiles a t position 3. The 3-carbaldehyde, from a Vilsmeier reaction, was converted into 1 -methoxy-NN-dimethyltryptamine. 1.5-Dirnethoxyindole underwent the Mannich reaction forming the 3-dimethylaminomethyl derivative. 1 -Acetoxyindole with dimethylforrnamide and phosphoryl chloride yielded 2-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…The first one is the simplest among the thus far reported syntheses. 10,25) Methylation of 8e, obtained from 6c in three steps, as described above, with CH 2 N 2 resulted in 5 in 57% yield. Thus, 5 is now available in four steps from 6c in 29% overall yield with 40% originality rate.…”
Section: Synthesis Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one is the simplest among the thus far reported syntheses. 10,25) Methylation of 8e, obtained from 6c in three steps, as described above, with CH 2 N 2 resulted in 5 in 57% yield. Thus, 5 is now available in four steps from 6c in 29% overall yield with 40% originality rate.…”
Section: Synthesis Ofmentioning
confidence: 99%
“…The first total synthesis of 5 by Acheson and co-workers 10) was carried out in thirteen steps from 2-nitroaniline (21) via such intermediates as 22 and 23 in 2.6% overall yield. We needed a simpler synthesis of 5 in order to Chart 1 Chart 2 begin a study of its derivatives and their biological activity.…”
Section: Synthesis Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we decided to verify the information that the reaction of peracetylated ribofuranose 13 with indoline (7) produces only 1-acetylindoline. 11 It was found that condensation of protected ribose 13 with 3 equivalents of indoline under reflux during 6 hours afforded the desired 1-(2,3,5-tri-O-acetyl-β-D-ribofuranosyl)indoline (14) in 63% yield after column chromatography in addition to the 1-acetylindoline (Scheme 2). We presented this result in 2003 on the 10 th Blue Danube Symposium on Heterocyclic Chemistry in Vienna.…”
Section: Resultsmentioning
confidence: 99%
“…1-Methoxyindole-3-carbaldehyde 5 (1, Scheme 2) is one of the simplest 1-methoxyindoles and a natural product, isolated from radish as a phytoalexin by Takasugi 6 and co-workers. They also isolated another phytoalexin, brassicanal A (2), from Chinese cabbage.…”
mentioning
confidence: 99%